(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Benchmarking is a crucial tool for assessing the disparity between one’s own performance and the optimal performance. Benchmarking can be applied across a diverse range of domains. This study employs benchmarking as a methodological approach to evaluate the performance of women entrepreneurship. The presence of women entrepreneurs serves as an indicator of the equitable development of a society. The government’s financial inclusion initiatives are designed to promote entrepreneurship among a significant portion of the female population within the country. The objective of this study is to analyse the impact of financial inclusion, along with other factors such as family circumstances, benchmarking, entrepreneurial motivation, and entrepreneurial intention, on women’s decision to pursue entrepreneurship as a career path. The purpose of this research study is to examine the correlation between financial inclusion schemes and women entrepreneurship, as well as to establish a causal relationship between the two variables. The independent variable in this context is the financial inclusion effort, while the dependent variable is women entrepreneurship. A study was conducted with a sample size of 350 women entrepreneurs. The sample was chosen based on its convenience. Among the entire sample